Technology and innovation policy : an international perspective - Cunningham, James A.; Link, Albert N. (New horizons in innovation management series, 2021)
"This book discusses technology policy and innovation policy from an international perspective, with a particular emphasis on the policies of the United States and the United Kingdom. The importance of these policy areas, as well as their relationship to one another, is a unifying theme throughout, and this relationship is illustrated through an integrating policy framework. Private sector and public sector investments in R&D are posited to be the relevant target variables for technology policy, and vehicles to provide incentives for making each more effective are discussed along with suggestive information about how effective incentives have actually been. Consideration is given to the unintended consequences of technology policy. Also emphasized is the environment in which technology policy is promulgated and its relationship to a global innovation ecosystem. Innovation policy is a consequence of technology policy, and the innovation policies of various countries are also discussed. Technology and Innovation Policy will benefit academic researchers, senior scientists, innovation and technology policy makers, and graduate students who seek a deeper understanding of the relationship between technology and innovation policies from an international perspective"--